Re-exploration of prognosis in type B thymomas: establishment of a predictive nomogram model - Ke Zhao; Lei Liu; Xiaoyun Zhou; Guige Wang; Jiaqi Zhang; Xuehan Gao; Libing Yang; Ke Rao; Chao Guo; Ye Zhang; Cheng Huang; Hongsheng Liu; et al. (World Journal of Surgical Oncology, 2024)
Abstract Objective To explore the risk factors for disease progression after initial treatment of type B thymomas using a predictive nomogram model. Methods A single-center retrospective study of patients with type B thymoma was performed. The Cox proportional hazard model was used for univariate and multivariate analyses. Variables with statistical and clinical significance in the multivariate Cox regression were integrated into a nomogram to establish a predictive model for disease progression. Results A total of 353 cases with type B thymoma were retrieved between January 2012 and December 2021. The median follow-up was 58 months (range: 1–128 months). The 10-year progression-free survival (PFS) was 91.8%. The final nomogram model included R0 resection status and Masaoka stage, with a concordance index of 0.880. Non-R0 resection and advanced Masaoka stage were negative prognostic factors for disease progression (p < 0.001). No benefits of postoperative radiotherapy (PORT) were observed in patients with advanced stage and non-R0 resection (p = 0.114 and 0.284, respectively). Conclusion The best treatment strategy for type B thymoma is the detection and achievement of R0 resection as early as possible. Long-term follow-up is necessary, especially for patients with advanced Masaoka stage and who have not achieved R0 resection. No prognostic benefits were observed for PORT.